Theoretical studies of preparation of core-shell nanoparticles by electrochemical metal deposition - Oviedo, Oscar Alejandro (2010)
In the present work we discuss the statistical mechanical framework for predicting the decoration of metallic nanoparticles using electrochemical methods, in thermodynamic equilibrium. It is found that depending on the interactions between the two metals, controlled decoration may be achieved for core-shell nanoparticles in undersaturation and oversaturation conditions. The concept of underpotential deposition is discussed for the case of nanoparticles, with the finding that this phenomenon may be size dependent.